High school circa '65 - De los Reyes, Maryo J.; Castillo, Bernardo S.; Salinas, Francisco C.; Tordesillas, Jake
The unity of a high school senior class is threatened by gossip about an affair between a respected biology teacher and a popular young new teacher.